2014
DOI: 10.1021/op400354g
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of a Nonracemic α-Arylpropionic Acid via Ketene Desymmetrization for a Glucokinase Activator

Abstract: Process research and development for a synthesis of the chiral carboxylic acid ( R )-2 as a key intermediate of the glucokinase activator ( R )-1 is described. The construction of the stereocenter at the α-carbon is a key point for the synthesis of ( R )-2. The proposed process utilizes desymmetrization of a ketene in situ generated from the corresponding racemic carboxylic acid Rac -2 with (R)-pantolactone as a chiral auxiliary followed by hydrolysis of the resulting ester. This key step has been success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Secondary and tertiary alcohols in positions α to amide or ester groups are efficiently reduced as shown in Scheme . Remarkably, Yamagami et al demonstrated that this process could be easily scale‐up to a kilogram‐scale to generate an advanced intermediate in the synthesis of a potent glucokinase activator (GKA) . The reaction may be sensitive to steric hindrance has shown by the modest yield obtained with the menthyl ester substrate which requires longer reaction time and heating.…”
Section: Iodine‐atom‐mediated Deoxygenationmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary and tertiary alcohols in positions α to amide or ester groups are efficiently reduced as shown in Scheme . Remarkably, Yamagami et al demonstrated that this process could be easily scale‐up to a kilogram‐scale to generate an advanced intermediate in the synthesis of a potent glucokinase activator (GKA) . The reaction may be sensitive to steric hindrance has shown by the modest yield obtained with the menthyl ester substrate which requires longer reaction time and heating.…”
Section: Iodine‐atom‐mediated Deoxygenationmentioning
confidence: 99%
“…However, under treatment with TFA and Et 3 SiH, Sundberg et al reported that competitive dehydration reaction could occur to give the corresponding conjugated alkene (Scheme a) . This methodology has also been applied to the formation of a key intermediate in the synthesis of a potent glucokinase activator (see Scheme ) . In this case, trifluoroacetic acid failed to promote the removal of the hydroxy group.…”
Section: Lewis and Brønsted Acid‐mediated Deoxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORTEP diagram 21 of 19 ( Figure 1) clearly showed the relative configuration of stereogenic centers resolving the structure of 17 as well as its diastereomer 18. Analogously, the asymmetric dihydroxylation reaction of 6 using the catalytic systems (DHQD) 2 PYR/OsO 4 /K 2 CO 3 /K 3 Fe(CN) 6 as well as (DHQ) 2 PYR/OsO 4 /K 2 CO 3 /K 3 Fe(CN) 6 provided the isomeric lactones 20 and 21 (Scheme 5). The lactones 17 and 20, thus constitute one enantiomeric set, which showed almost identical spectral data and identical specific rotation value with opposite sign.…”
Section: A R T Ic Le In F O Abstractmentioning
confidence: 99%
“…TES-promoted reactions that involve metal catalysts (Pd, Mo, Ni, Au, Mn or Ru complexes) have been successfully used for the regioselective hydrogenation of olefins, [22][23][24] imines, [25] nitriles, [26] nitro derivatives [27] and carbonyl compounds. [28][29][30][31] Alternatively, TES mixed with a suitable Brønsted acid can be used under metal-catalyst-free conditions, [32][33][34][35] e.g., for the reductive cleavage of sulfides, [36] ethers, [37,38] hydroxides [39,40] and acetoxy groups. [41] A TES/trifluoroacetic acid (TFA) mixture can also be used as the reducing agent to yield unsaturated heterocycles.…”
Section: Introductionmentioning
confidence: 99%